EVALUASI PENGARUH PEMBERIAN BAHAN PENGAWET TERHADAP LAPISAN FINISHING EKSTERIOR KAYU PINUS DAN JATI RAKYAT - Fauzan Fahrussiam; Andi Tri Lestari (Fakultas Pertanian Universitas Mataram, 2023)
Woods that were placed outdoors were exposed to UV-induced photodegradation processes which damaged the lignin bonds in the wood resulting in the more susceptible woods against abrasion and weathering. This circumstance led to more finishing processes by applying paint to the wood surface carried out by industries and at the home level. Some finishing materials not only contribute to increasing the aesthetics of the wood surface but also increased the wood's resistance against harmful microorganisms. On the other hand, the resistance against pests did not increase as high as the resistance against outdoor weathering. In this study, pine woods and teak woods collected from the community forest were soaked in cold borax solution as a preservative agent before applying the paint to the wood surface. The treatments applied to the samples in this study were untreated control samples, preservative-treated samples, finishing-treated samples, and both preservative and finishing-treated samples. The results of this study showed that both teak and pine wood with preservative and finishing treatment were resistant to microbial damage (0% damage) after left 8 weeks of exposure in the outdoor area. However, there is a need to conduct further research with longer exposure time (1-2 years) to get more significant result differences between each treatment.